PRODUCTION OF QUININE ALKALOID BY SOME ENDOPHYTIC MICROBES WITH ADDITION OF INDUCER SUBSTANCES (Studies on Endophytic Microbes of Cinchona sp. plants (2)) - Simanjuntak, Partomuan; Parwati, Titi; ., Bustanussalam; Prana, Titik K.; Shibuya, Hirotaka (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2002)
Endophytic microbes have been known to be potential as the sources of active compound for medicines. Optimization of medium, including of inducer addition, is necessary to obtain optimum products. This study, therefore, was aimed to investigate the effect of Cinchona succirubra bark powder addition in the production of quinine compound by endophytic microbe growing in two different liquid media. Endophytic microbe isolated from Cinchona sp. were shaker incubated in Potato Dextrose Broth (PDB) and Phoma media with the addition of bark powder of C. succirubra for 3 days. Quinine production was analyzed with High Performance Liquid Chromatography (HPLC). The result showed an increasing of quinine production for each microbes. Highest increasing of quinine production (2.2 folds) was yielded by mold culture (J3P1) grown in PDB medium.Keywords: inducer, quinine, endophytic microbe, Cinchona succirubra